Analysis of Customer Satisfaction at Coffee Shops Using the Quality Function Deployment (QFD) Approach Integrated with the Importance-Performance Analysis (IPA) Method - Putri, Nadya Novianti Dwi; Ningsih, Arum Rovarti; Nasution, Addiena Syahvina; Endyra, Fadlila; Ihsan, Fikratul; Masyitah, Masyitah (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Coffee Shop XYZ is a coffee shop located in Lampung that provides a space for people from all walks of life to meet and gather with friends. This shop focuses on service quality because service is one of the factors that influence customer satisfaction. This study focuses on the services provided at the coffee shop using the Quality Function Deployment (QFD) method integrated with the Importance-Performance Analysis (IPA) method. This study integrates the IPA and QFD approaches as strategic tools for coffee shop management to transform findings regarding service weaknesses into concrete, systematic, and measurable technical action plans. The result of this QFD development is a House of Quality (HoQ), which contains information regarding the design and development of products or services aimed at identifying value gaps in customer satisfaction levels through the creation of a Planning Matrix within the QFD method. This study involved 100 respondents, each of whom was a general coffee shop consumer and a consumer of Coffee Shop XYZ. The results of this study indicate that there are 10 attributes that do not yet meet consumer expectations because they still have negative values, and a priority order for improvements was derived from the technical responses of Coffee Shop XYZ to enhance consumer satisfaction, particularly regarding service quality, as it has a strong relationship with consumer needs; thus, it is expected that these attributes will make a significant contribution.